(untitled) (Journal of Renal and Hepatic Disorders, 2017)
Tenofovir, a third generation oral nucleos(t)ide analogue, currently represents one of the first-line drugs recommended for treating chronic hepatitis B virus (HBV) infection. After oral administration, tenofovir is mostly excreted in the urine by glomerular filtration and proximal tubular secretion. Hence, an impaired kidney function may lead to an increased renal exposure to the drug in patients with coexistent renal damage. This could further worsen kidney disease through different mechanisms of nephrotoxicity such as mitochondrial DNA depletion and tubular cytotoxicity. Despite several studies performed so far to assess tenofovir-related renal toxicity, data in HBV patients are not yet conclusive. Screening of risk factors for kidney disease before starting therapy and a careful monitoring of serum creatinine, glomerular filtration rate, serum phosphate and urine analysis during treatment are advocated to adjust the dose or stop treatment if needed. New biomarkers of tubular injury, such as neutrophil gelatinase associated lipocalin, could become helpful in the future for the timely identification and risk stratification of renal damage induced by tenofovir.